Estimativa e análise de índices de irregularidades da ionosfera utilizando dados GPS de redes ativas - Pereira, Vinícius Amadeu Stuani [UNESP]; Camargo, Paulo de Oliveira [UNESP] (FapUNIFESP (SciELO), 2013)
Observable GNSS (Global Navigation Satellite System) are affected by systematic errors due to free electrons present in the ionosphere. The error associated with the ionosphere depends on the Total Electron Content (TEC), which is influenced by several variables: solar cycle, season, local time, geomagnetic activity and geographic location. The GPS (Global Positioning System), GLONASS (Global Orbiting Navigation Satellite System) and Galileo dual frequency receivers allow the calculation of the error that affects the GNSS observables and the TEC. Using the rate of change of TEC (ROT - Rate of TEC) indices that indicate irregularities of the ionosphere can be determined, allowing inferences about its behavior. Currently it is possible to perform such studies in Brazil, due to the several Active Networks available, such as RBMC/RIBaC (Rede Brasileira de Monitoramento Contínuo/Rede INCRA de Bases Comunitárias) and GNSS Active Network of São Paulo. The proposed research aimed at estimating and analysing of indexes of irregularities of the ionosphere, besides supplying the geosciences of information about the behavior of the ionosphere.
Estimation and analysis of the ionosphere irregularities indices using GPS data from active networks
Keywords: Active networks; GNSS; Indexes of irregularities of the ionosphere; Ionosphere; ROT; electron; geomagnetism; GLONASS; GPS; ionosphere; solar cycle; Brazil